Pharmaceutical care and medication adherence in management of psychosis in a Nigerian tertiary hospital - Jonathan Danladi; Kakjing D Falang; Raymond A Barde; Nanlok S Jimam; Dauda A Dangiwa; Hafsat O Jimoh (Wolters Kluwer Medknow Publications, 2013)
Objective: The primary objective of this study is to examine the medication adherence levels (as a function of pharmaceutical care) and its contributing factors in schizophrenic patients receiving antipsychotic drugs. Methods: This was a cross-sectional study administering a structured questionnaire to 231 patients. Adherence was measured through patient self-reporting. Association between independent variables and adherence to antipsychotics were measured through odds ratios (OR) in the univariate analysis while the best predictors of adherence were determined through the multiple logistic regressions. Findings: Adherence level was found to be 65.8% (95% confidence interval [CI]: 59.3-71.9%). The following factors were identified to be associated with adherence in the univariate analysis: age (OR 1.088), sex (OR 1.231), employment (OR 0.366), marital status (singles, OR 0.022), drug adherence counseling (OR 11.641), twice a day frequency (OR 8.434), alcohol non-intake (OR 1.469), educational level (primary OR 1.9312, secondary OR 11.022, tertiary OR 4.771), occupation (public servant 6.273). In the multivariate analysis, age, three times a day frequency of drug intake, singles and educational levels such as primary, secondary or tertiary school, strongly affected adherence (P < 0.05). Conclusion: Although patients adherence level was high (65.8%), there is a need to emphasize that pharmacists spend more time in counseling and educating patients, especially younger ones on drug adherence before any antipsychotic medications are dispensed. Furthermore, patients should be taught the use of adherence devices such as reminders so that adherence to antipsychotic medications can be optimized.